Evaluasi Penggunaan Lembar Kerja Peserta Didik (LKPD) berbasis Problem Based Learning di Kalangan Mahasiswa : Studi Pengembangan di Universitas Islam Negeri Sultan Syarif Kasim Riau - Annisa, Annisa Fazila Sabrina Damanik; Berlian, Mery; Alaniyah Syafaren (Milenial: Journal for Teachers and Learning, 2024)
Student worksheets (LKPD) are sheets containing assignments that must be done by students. Activity sheets are usually in the form of instructions, steps to complete a task. The advantage of using LKPD is that it makes it easier for educators to carry out learning, for students to learn independently and learn to understand and carry out a written assignment. This study aims to evaluate the use of Student Worksheets (LKPD) based on Problem Based Learning (PBL) among students as an educational event. The type of research used in this research is R&D (Research and Development) with the ADDIE development model proposed by Lee & Owens (2004). The research was conducted by involving 58 respondents, including 3 lecturers, 20 teachers and 35 students. The data collection tool used is an online questionnaire consisting of 5 constructs with 27 questions with a cronbach alpha of 0.941. The data that has been collected is then analyzed using the help of the SPSS program version 23.00 for Windows. The results of the study show that student evaluation of the use of LKPD in the five constructs includes: 1). Suitability of LKPD and the learning model used (4.06) in the "good" category 2). Appropriate use of LKPD and learning methods (4.08) in the "good" category 3). Completeness and arrangement of descriptions on LKPD (4.17) in the "good" category 4). Use of language, spelling of words and sentences (4.03) in the "good" category 5). The graphical component (4.09) is in the "good" category and has an overall average of 4.08 in the "good" category. Thus, educators and prospective educators are expected to be able to produce interesting and effective learning media.